Effectiveness of Spiritual Emotional Freedom Technique (SEFT) Therapy in Reducing Symptoms and Signs of Patients with Violent Behavior Risk - Sahara, Dita; Herliana, Irma; Rizal, Ahmad (Universitas Pendidikan Indonesia, 2024)
Introduction: The risk of violent behavior is a vulnerability to behavior that shows the potential for physical and emotional harm to oneself, others, and the environment. Spiritual Emotional Freedom Technique (SEFT) is a therapy that uses simple finger tapping on specific meridian points of the body to help solve physical and psychological problems. This therapy combines psychological energy with spiritual strength, so that SEFT, in addition to being a healing technique, also automatically leads a person into a spiritual realm that connects them to their God. Objective: This study aims to determine the effect of SEFT on the signs and symptoms of the risk of violent behavior in the Women's PHCU Unit. Method: This study used a pre-experimental design with a pre-test-post-test non-equivalent control group design. The study used 17 samples in the intervention group and 17 samples in the control group. This study used Positive and Negative Syndrome Scale - Excited Component (PANSS – EC) to assess signs and symptoms of risk of violent behavior. Result: The results showed a p-value of 0.000 (0.05), indicating that SEFT had an effect on the signs and symptoms of patients at risk of violent behavior. Conclusion: SEFT is very beneficial for reducing the signs and symptoms of patients at risk of violent behavior.